Zero-Trust Architecture for Securing Multi-Cloud Environments (Cybersecurity and Network Defense Research, 2022)
The proliferation of multi-cloud environments has rendered traditional perimeter-based security models obsolete, necessitating the adoption of a Zero-Trust Architecture (ZTA) to mitigate evolving cyber threats. This paper explores the implementation of ZTA in multi-cloud infrastructures, emphasizing the principles of strict identity verification, granular access control, and continuous monitoring. It examines security challenges such as lateral movement, unauthorized access, and cloud-native attack vectors, demonstrating how ZTA enforces least-privilege access and micro-segmentation to fortify cloud workloads. Furthermore, it evaluates policy enforcement mechanisms, identity and access management (IAM), and the role of artificial intelligence in adaptive threat detection. Case studies illustrate successful ZTA deployments in securing multi-cloud ecosystems, highlighting their effectiveness in reducing attack surfaces. The study concludes with an analysis of performance trade-offs and best practices for enterprises transitioning to a zero-trust security paradigm.